In vitro effects of 2‐methyl‐3‐propylbutane‐1, 4‐diol purified from Alstonia boonei on erythrocyte membrane stabilization and mitochondrial membrane permeabilization. (15th November 2022) - Olanlokun, John Oludele; Oyebode, Olubukola Titilope; Popoola, David; Bodede, Olusola; Idowu, Thomas Oyebode; Moodley, Roshila; Olorunsogo, Olufunso Olabode
Abstract: A recent review on the ethnomedicinal, chemical, pharmacological, and toxicological properties of Alstonia boonei revealed the plant's potential in the treatment and management of a range of diseases. However, most of these pharmacological effects are only traceable to the crude form of the plant extract and not specific natural products. Phytochemical investigation of the methanol fraction of the methanol extract of the stem‐bark of Alstonia boonei led to the isolation and identification of 2‐methyl‐3‐propylbutane‐1, 4‐diol. The structures were elucidated by the application of 1D‐, and 2D‐NMR spectroscopic analyses and by comparison with literature data. In this study, the membrane stabilizing activity, mitochondrial membrane permeability transition pore opening, cytochrome c release, mitochondrial ATPase activity, and prevention of mitochondrial lipid peroxidation activity of 2‐methyl‐3‐propylbutane‐1, 4‐diol (MPBD) isolated from A. boonei were determined. The results showed that MPBD significantly ( p  < .05) prevented peroxidation of mitochondrial membrane lipids and hemolysis using both the heat‐induced and hypotonic solution‐induced membrane stabilization assays. On the contrary, the compound caused large amplitude swelling of rat liver mitochondria in the absence of calcium, significant ( p  < .05) cytochrome c release and enhancement of mitochondrial ATPase activity in vitro . Our findings suggest that MPBD showed characteristic biological properties useful in modulating cell death. Abstract : Alkane diol purified from Alstonia boonei has modulatory effects on mitochondria, enhance mitochondrial ATPase activity and cytochrome c release; it also prevented hemolysis.